Optimisation of PID controller for load frequency control in two-area power system using evolutionary particle swarm optimisation - Illias, Hazlee Azil; Zahari, A.F.M.; Mokhlis, Hazlie (Engineering and Scientific Research Groups, 2016)
The main objectives of load frequency control (LFC) are to regulate the electrical power supply in two-area power system and change the system frequency and tie-line load. The performance of LFC has to be tuned properly so that its performance can be optimised. However, most of the tuning processes are performed through trial and error until the best performance is achieved. Therefore, to overcome this situation, in this work, particle swarm optimization (PSO) and evolutionary particle swarm optimization (EPSO) algorithms were employed in a LFC of twoarea power system to optimise the performance of the PID controller. The purpose of using PID controller is to improve the performance of the LFC. Comparison of the performance using PSO and EPSO was made to identify which algorithm is better in controlling the performance of the LFC. It was found that using EPSO, the performance of the LFC is better in terms of settling time and rise time than using PSO. Hence, by implementing an optimisation method, the performance of the LFC can be optimised through optimising the PID controller parameters.